Freedom and Solidarity: Some Remarks in Light of the Contemporary Reception of Hegel - Filipe Campello (Ethic@: an International Journal for Moral Philosophy)
This paper concerns the question of the relationship between emotions and justice which has been increasingly found in the literature in the past years. Having in view empirically informed works on the role of emotive and affective contents on social practices, decision-making processes and on the constitution of moral judgments as background, the core idea we find in this debate is that the descriptive validity of a social theory depends on the analyses of the constitutive role of emotions and affects on social spheres. On the other hand, I want to suggest that Hegel can contribute towards a normative potential of those analyses through the approach of an articulation of the formative character of institutions, oriented by what can be understood as the institutional mediation of individual freedom through the idea of socially inclusive, “decentralized will”. Regarding this nexus between emotions and justice I will, in this paper, focus on the discussion of these ideas regarding the civil society, where I will briefly develop my argument in three short steps. Firstly, I will briefly suggest in what sense Hegel could help us in discussing the role of emotions for a social theory. In a second step I will point out a specific, emotional component in the sphere of civil society, namely, the relationship between passions and interests. Finally, I will connect this idea to a peculiarity based on Hegel’s concept of solidarity related to his idea of the formation of Will (“Willensbildung”), arguing that the concept of social justice depends not only on rational guided actions, but also in how far an institutional framework enables a volitional dimension that is justified, on one hand, by the satisfaction of individual needs and, on the other, by the sentiment of cooperation.